Hubungan Antara Kebiasaan Membaca Siswa dan Menulis Teks Narasi - Rijal, Khairul; Efendi, Zuhri (STKIP Siliwangi, 2024)
This study is conducted to know the correlation between reading habits and students’ writing ability. The method used is a correlation study. The respondents are fourth-semester students at STKIP Muhammadiyah Aceh Barat Daya. The total number of respondents is 30 students. The data were collected by using two techniques; a questionnaire as an instrument to survey students’ reading habits and a test to measure students’ writing skill. Pearson Product Moment was implemented to see whether reading habits correlate with students’ ability to write narrative text. The result of the study proved that the significance (Sig. 2-tailed) value is 0.000 which indicates a significant relationship. There is a strong correlation between students' reading habits and their writing ability. Therefore, it is suggested to enhance students' reading habits to improve their writing skills.